Implementasi pendidikan adab di Ma’had Aly Ki Bagus Hadikusumo Sukoharjo - Muh. Fatahillah Suparman; Muhammad Isa Anshory; Ngatmin Abbas (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to explore the urgency and implementation of adab in Ma'had Aly Ki Bagus Hadikusumo Sukoharjo. The methodology used is a qualitative approach with data collection techniques through observation, interviews, and document studies. The results of the study indicate that adab has an important urgency in shaping good character and noble ethics of the students, and preparing them to make positive contributions to society. Adab is implemented through various ways, such as habituation and practice of adab in daily activities, the implementation of religious lectures and discussions, as well as the formation of a culture of clean, healthy, and tidy environments. However, the research also shows that the implementation of adab in Ma'had Aly Ki Bagus Hadikusumo Sukoharjo still has shortcomings, such as a lack of supervision and discipline enforcement towards violations of adab. Therefore, better efforts are needed to implement adab so that the desired Islamic education goals can be achieved optimally